Patterns of Phenotypic Evolution Associated with Marine/Freshwater Transitions in Fishes. (8th June 2022) - de Brito, Victor; Betancur-R, Ricardo; Burns, Michael D; Buser, Thaddaeus J; Conway, Kevin W; Fontenelle, João Pedro; Kolmann, Matthew A; McCraney, W Tyler; Thacker, Christine E; Bloom, Devin D
Abstract: Evolutionary transitions between marine and freshwater ecosystems have occurred repeatedly throughout the phylogenetic history of fishes. The theory of ecological opportunity predicts that lineages that colonize species-poor regions will have greater potential for phenotypic diversification than lineages invading species-rich regions. Thus, transitions between marine and freshwaters may promote phenotypic diversification in trans-marine/freshwater fish clades. We used phylogenetic comparative methods to analyze body size data in nine major fish clades that have crossed the marine/freshwater boundary. We explored how habitat transitions, ecological opportunity, and community interactions influenced patterns of phenotypic diversity. Our analyses indicated that transitions between marine and freshwater habitats did not drive body size evolution, and there are few differences in body size between marine and freshwater lineages. We found that body size disparity in freshwater lineages is not correlated with the number of independent transitions to freshwaters. We found a positive correlation between body size disparity and overall species richness of a given area, and a negative correlation between body size disparity and diversity of closely related species. Our results indicate that the diversity of incumbent freshwater species does not restrict phenotypic diversification, but the diversity of closely related taxa can limit body size diversification. Ecological opportunity arising from colonization of novel habitats does not seem to have a major effect in the trajectory of body size evolution in trans-marine/freshwater clades. Moreover, competition with closely related taxa in freshwaters has a greater effect than competition with distantly related incumbent species.